Kestabilan Estimasi Parameter Kemampuan pada Model Logistik Item Response Theory Ditinjau dari Panjang Tes - Ilham Falani; Siti Ayu Kumala (Universitas Indraprasta PGRI Jakarta, 2017)
This study aims to test the stability of ability parameter estimation of Logistic Parameter ItemResponse Theory (IRT) model based on the length of test used. Logistic Parameter Model used in thisresearch is 2 Logistic Parameter (2PL) Model. The data used are simulation data generated by usingWingen software, with sample size of 1000 participants with variation of test length used is 20, 40, and60. The estimation is then made for each length of the test by using Wingen software with replicationsfor 10 times. Based on the results of the analysis on the estimation results, it can be seen that thelonger the test is used, the more accurate estimation of ability parameter of 2PL model is.